Partial sleep restriction impairs static postural control in elite judo athletes - Souissi, N.; Zouita, A.; Abedelmalek, S.; Trabelsi, K.; Clark, C. C. T.; Dziri, K.; Chtourou, H. (Biological Rhythm Research, 2020)
The present study evaluates the effect of partial sleep restriction on postural control in judokas. Fourteen elite-level judokas performed three static postural control tests (the Unilateral Stance (US, on the Right and Left Foot); the modified Clinical Test for the Sensory Interaction on Balance (mCTSIB, on a firm and an unstable surface) stance with the eyes opened and then closed, and the Weight-Bearing Squat test (WBS)) after (i) a reference-normal-sleep-night (RN) and (ii) 4-h of partial sleep restriction at the end (SREN) (i.e., sleep from 22h30 to 03h00) or the beginning (SRBN) (i.e., sleep from 03:00h to 07:00h) of the night. Concerning US, sway velocity increased significantly after SRBN and SREN, in comparison with RN (p < 0.001) and was significantly higher in closed vs. open eyes during SRBN, SREN and RN (p < 0.001). For mCTSIB, sway velocity increased significantly during SBND and SRBN, compared to RN (p < 0.001) and was higher with eyes open than eyes closed in the foam surface during SRBN, SREN and RN (p < 0.0001). For WBS, there were no significant between conditions differences. In conclusion, partial sleep restriction of 4-h may negatively affect the postural control of judokas.